Situational and motivational factors affecting Willingness to communicate among esl students - Anna Lynn Abu Bakar; Suyansah Swanto; Romzi Ationg; Wardatul Akmam Din (ResearchGate, 2022)
Having a sense of willingness to communicate in the 2nd language (L2) is one of the important factors in improving L2 speaking skills. Willingness to Communicate (WTC) a model proposed by MacIntyre et. al (1998) is considered an indicator for successful English learning outcome. There are several factors that influences students’ WTC in English. Hence, the objective of this study is to look into the individual factors that influences pre-university students WTC in English in an ESL digital classroom setting. The result of the study was obtained through the use of qualitative method using a focused group interview of 25 voluntary pre-university students in a public university in Sabah, Malaysia. The data obtained revealed that individual factors which are self-confidence, language anxiety, motivation and grit play a role in influencing pre-university students’ WTC in English. This finding would be beneficial to language instructors as well as syllabus makers in providing and designing an English lesson that is geared to encouraging students to communicate in English.